Implikasi Pendidikan dari Al-Qur’an Surat An-Nahl Ayat 43-44 tentang Tugas Rasul sebagai “Ahlu Dzikri” terhadap Peran Guru sebagai Sumber Pengetahuan - Ade Nandar; Enoh; Fitroh Hayati (UNISBA Press, 2022)
Abstract. The prophet Muhammad (peace and blessings be upon him) was opposed by the idolaters. Thus, Allah SWT sent down the letter an-Nahl verse 43-44. Allah commanded the uninved to ask the Dzikri, and it was revealed to the prophet Muhammad adz-Dzikr to explain to the people what has been revealed to them so that they may think. This research uses descriptive-analytical methods of collection techniques, namely literature (library research) by studying in depth various interpretations, books and articles related to the subject matter of the research. The implication contained in the Qur'an Surah An-Nahl verses 43-44 is (1) A teacher must become ahlu dzikri, mastering the knowledge to be taught to his learners. (2) A teacher must understand the main duties, functions and roles of the teacher because the teacher not only teaches in the classroom but assumes the responsibility to educate, guide, foster, direct, train, assess, evaluate learners. (3) Allah's Apostle is a good role model for a teacher in carrying out the duties, functions and roles of teachers. Because the duty of the teacher is the same as the duty of the Prophet (peace be upon him) to his people. (4) A good teacher is one who can read and understand the meaning of the Qur'an. (5) The teacher is a source of knowledge for learners both in his words, deeds, and decrees so that it becomes the benchmark of learners in learning therefore a teacher must really understand the teacher's code of ethics. Abstrak. Kerasulan nabi Muhammad SAW ditentang oleh kaum musyrikin. Maka Allah SWT menurunkan surat an-Nahl ayat 43-44. Allah memerintahkan kepada orang yang tidak berpengatahuan agar bertanya kepada Ahli Dzikri, dan diturunkan kepada nabi Muhammad adz-Dzikr untuk menjelaskan kepada manusia apa yang telah diturunkan kepada mereka agar mereka berfikir. Penelitian ini menggunakan metode deskriptif-analitis teknik pengumpulan yaitu kepustakaan (library research) dengan mengkaji secara mendalam berbagai tafsir, buku dan artikel yang berhubungan dengan pokok masalah penelitian.Implikasi yang terdapat dalam Al-Qur’an Surat An-Nahl ayat 43-44 adalah (1) Seorang guru harus menjadi ahlu dzikri, menguasai ilmu yang akan diajarkan kepada peserta didiknya. (2) Seorang guru harus memahami tugas pokok, fungsi dan peran guru karena guru bukan hanya mengajar di kelas akan tetapi memikul tanggung jawab untuk mendidik, membimbing, membina, mengarahkan, melatih, menilai, mengevaluasi peserta didik. (3) Rasullah SAW adalah panutan yang baik bagi seorang guru dalam menjalankan tugas, fungsi dan peran guru. Karena tugas guru sama seperti tugas Rasulullah SAW terhadap umatnya. (4) Seorang guru yang baik adalah yang dapat membaca dan memahami makna Al-Qur’an. (5) Guru adalah sumber pengetahuan bagi peserta didik baik dalam perkataannya, perbuatannya, maupun ketetapannya sehingga menjadi patokan peserta didik dalam belajar maka dari itu seorang guru harus benar-benar memahami kode etik guru.